Clinical-epidemiological profile of people submitted to cataract surgery at a health service in Palmas/Tocantins (Research, Society and Development, 2023)
Cataract is defined as any clouding of the crystalline lens that prevents adequate light from entering the eye, which may lead to decreased visual acuity and blindness. In Brazil, there are approximately 6.5 million visually impaired people and an estimated 1.5 million blind people, of which approximatelyThis article aims to evaluate the epidemiological profile of patients undergoing cataract surgery, identifying the surgical ophthalmological benefits in order to subsidize the formulation of public policies to expand the supply of surgeries. This is an observational, descriptive, cross-sectional study with retrospective data collection carried out through the review of medical records of patients who underwent cataract surgery in a service accredited by the SUS in Palmas, Tocantins, in the period of January 2019 to December 2021. The conclusion of the study is that most cataract surgical patients are between 61 and 80 years old (79.81%), with the largest number of patients between the 71st and 80th years (41.26%), with a slight prevalence of males (51.85%), while females accounted for 48.19%. Regarding the morbidities and chronic diseases associated with patients who underwent cataract surgery, systemic arterial hypertension and Diabetes Mellitus. In this analysis, it was possible to notice that 80.42% of the sample showed a significant improvement in the analysis of the results, and the most common classification was Cortinuclear associated with posterior subcapsular in 52.08% of the patients, followed by 38% of corticonuclear. 25% had White Cataract. None of the surgeries presented complications after the surgical procedure.